The Rules of How Reality Works Through the Prism of Post-Postmodern Prose: (D.I. Drozdovskyi, "Problematic-Thematic Units and Philosophical-Esthetical Parameters of the British Post-Postmodern Novel" ["Проблемно-тематичні комплекси й філософсько-естетичні параметри британського постпостмодерністського роману"]. Kiev: Samit-knyha, 2020) - Zymomria, Mykoła (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The reviewer analyses the monograph Problematic-Thematic Units and Philosophical-Esthetical Parameters of the British Post-Postmodern Novel (Kyiv, 2020) written by Dmytro Drozdovskyi, a Ukrainian scholar from Taras Shevchenko Institute of Literature of the National Academy of Sciences of Ukraine, member of The European Society for the Study of English (Bulgarian branch). In the monograph, the author has outlined the theory of the post-postmodern novel based on the analysis of the key novels of contemporary British fiction (David Mitchell, Ian McEwan, Sarah waters, Mark Haddon, etc.). The review states that the Ukrainian scholar has developed the theory proposed by Fredric Jameson regarding the post-postmodern features of Cloud Atlas and also discusses the concept of meta-modernity as one of the sections in the post-postmodern literary paradigm in the UK. Drozdovskyi argues that meta-modernism cannot be the only term that explains all the peculiarities of contemporary British fiction, which also cannot be outlined as meta-modern but as post-postmodern. The scholar provides a new theory of the novel based on the exploitation of real and unreal historical facts and imagined alternative histories and multifaceted realities. Furthermore, the reviewer pays attention to the contribution this monograph has for world literary studies spotlighting the theory of literary meta-genre patterns, as Drozdovskyi provides a theory according to which literary periods can be divided into those in which the carnival is the dominant meta-genre pattern (like postmodernism) and those that exploit the mystery as the meta-genre pattern (post-postmodernism). The reviewer analyses the key thematic units explained by Drozdovskyi as the key ones that determine the semiosphere of the contemporary British novel (post-metaphysical and post-positivist thinking of the characters, medicalisation of the humanitarian discourse, and the representation of the temporal unity of different realities). The scholar also states that the post-postmodern British novel exploits the findings of German Romanticism and Kant’s philosophy.